Terahertz spectrum-based refractive index sensor for brain lesion detection using photonic crystal fibers - Md. Naimur Rahman Naim; Jabin Tasnin Upoma; A. H. M. Iftekharul Ferdous; Kayab Khandakar; Md. Golam Sadeque; Md. Sohel Rana (PLoS ONE, 2025)
Numerous types of brain lesions, cancers, and tumors are still thought to be lethal. An accurate photonic-based biological sensor that is capable of differentiate between normal and pathological brain tissues is presented in this work. Here, we use the defective two-dimensional photonic crystal to theoretically investigate the brain lesion detection. By monitoring the red shift of the wavelength of resonance that occurs as the layer of cerebral lesions’ RI (Refractive Index) shifts from 1.38 to 1.4591, the device’s execution is confirmed. The outcomes of the simulation using the proposed detector architecture yield very high relative sensitivity values of 98.54%, 98.84%, 99.049% and 97.075%; low EML values of 0.00359 cm-1, 0.00323 cm-1, 0.00297 cm-1, 0.00533 cm-1 for Low Grade Glioma, Glio-blastoma, Lymphoma and Normal brain cell, respectively, at a 2.2 THz frequency regime. Furthermore, the simulation results for each of the cancer cases stated point to a remarkably minimal CL (Confinement Loss) of 6.315 ×  10-15 dB/cm. Through its ability to sense even minute fluctuations in RI, our planned sensor facilitates the identification of tumor at low concentrations. Because of its rapid reflexes, it can monitor the quantities of Low Grade Glioma, Glio-blastoma, Lymphoma and Normal brain cell instantly, which is essential to act rapidly in dangerous situations. In general, the efficacy, accuracy, and versatility of newly developed PCF sensors make them valuable tools for the reliable detection of Low Grade Glioma, Glio-blastoma, Lymphoma and Normal brain cell in a range of contexts, enhancing safety and surveillance protocols.